Mediações tecnológicas do rádio pela internet: identidades de pertencimento na escuta do programa “Sábado de todas as maneiras” - Costa, Claudiene dos Santos (2023)
This is an investigation into how the internet transmission of the radio program “Saturday in every way” acts on the sense of belonging of listeners to the city of Sobral, Ceará (Brazil). The program has been broadcast in analog format for 26 years, currently on 100.1 Tupinambá FM, and for at least seven years it has been broadcast simultaneously on the personal Facebook page of its presenter Tupinambá Marques. In a humorous tone, the program talks about local stories, facts and a collective memory (HALBWACHS, 2013)⁠, in northeastern Brazil, which implies proximity of listeners to those themes, as a sharing of repertoire is necessary for humor to be made intelligible and generate laughter (BERGSON, 2020)⁠. In the media convergence culture (JENKINS, 2015)⁠, the narrative construction of radio remains based on a sound basis but is complemented by multiplatform transmission multimedia content, referred to as hypermedia radio (LOPEZ, 2010)⁠ or expanded (KISCHINHEVSKY, 2012)⁠. Thus, the possibilities of interaction are increased and, in this case, of the experience of aspects of their identities linked to the place of origin, including for migrants. According to the Quadripolar Research Methodology (GOUVEIA; SILVA, 2023)⁠, suitable for investigations within the scope of Infocommunication (PASSARELLI; SILVA; RAMOS, 2014)⁠, we present the epistemological, theoretical, morphological and technical poles of the treatment of this object, passing through virtual ethnography (HINE, 2017)⁠ to record listeners' participation in the program's editions on Facebook regarding the links maintained with the city. Following precepts of the Reception Studies (GARCÍA CANCLINI, 2006; MARTÍN-BARBERO, 2013)⁠, we analyze mediations (MARTÍN-BARBERO, 2013)⁠ of aspects of cultural identities (HALL, 2020)⁠ of the public, and we also used content analysis (BARDIN, 2016)⁠ of questionnaires (GERHARDT; SILVEIRA, 2009)⁠⁠ with online listeners. As for the effects of exposure to the media (IGARTUA, 2021)⁠ we observed a predominance of emotional and physiological types⁠ (POTTER, 2012) , in addition to types of media mediation (LOPES, 2018; MARTÍN-BARBERO, 2018) and multimediations (OROZCO GÓMEZ, 2011), conditioned by the cyberculture technologies. We conclude that, among listeners of “Saturday in every way”, the use of internet radio cohabits with its analogue format, maintaining the latter's affection and proximity to the presenter and the contents presented, and using those multimedia resources in favor of, living whether or not in the program's theme city, maintaining a sense of home and community, having a common unifying media in the media ⁠(SOUSA, 2010) that reinforces territorial identity and meets affective and integration needs.